2019
DOI: 10.1109/access.2019.2934980
|View full text |Cite
|
Sign up to set email alerts
|

A Hierarchical Neural Hybrid Method for Failure Probability Estimation

Abstract: Failure probability evaluation for complex physical and engineering systems governed by partial differential equations (PDEs) are computationally intensive, especially when high-dimensional random parameters are involved. Since standard numerical schemes for solving these complex PDEs are expensive, traditional Monte Carlo methods which require repeatedly solving PDEs are infeasible. Alternative approaches which are typically the surrogate based methods suffer from the so-called "curse of dimensionality", whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…A comparative study using various mathematical examples shows that the method can obtain a more accurate percentile value estimation. Li et al [42] presented a novel hierarchical neural hybrid method to efficiently compute failure probabilities of challenging high-dimensional problems. Multi-fidelity surrogates are constructed based on two-hidden layer MLP with different levels of layers, so expensive high-fidelity surrogates are adapted only when the parameters are in the suspicious domain.…”
Section: Mlp-based Mcsmentioning
confidence: 99%
“…A comparative study using various mathematical examples shows that the method can obtain a more accurate percentile value estimation. Li et al [42] presented a novel hierarchical neural hybrid method to efficiently compute failure probabilities of challenging high-dimensional problems. Multi-fidelity surrogates are constructed based on two-hidden layer MLP with different levels of layers, so expensive high-fidelity surrogates are adapted only when the parameters are in the suspicious domain.…”
Section: Mlp-based Mcsmentioning
confidence: 99%
“…If we consider equal offline sample sizes, number of blocks and training epochs, N i = N off , B i = B off , T i = T off for all subdomains {D i } p i=1 , then total cost can be written as pN off B off T off C solve . The total cost is decreased by employing the idea of hierarchical neural networks [29,17]. Remark 2.…”
Section: D3m Summarymentioning
confidence: 99%
“…Fernandez et al 3 employed artificial neural networks as a surrogate model to transfer atomistic grain boundary decohesion data to continuum scale modeling of intergranular fracture in Aluminum. Li et al 4 developed a hierarchical neural hybrid method to efficiently compute failure probabilities in high dimensional problems employing the multifidelity approach introduced by Aydin et al 1 . They showed that for achieving an accurate estimate of the rare failure probability, a traditional Monte Carlo method needs to solve the equations significantly more frequently than the proposed hierarchical neural hybrid method.…”
Section: Introductionmentioning
confidence: 99%